2020
DOI: 10.3390/rs12101574
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Segmentation and Classification for Urban Village Using a Worldview Satellite Image Based on U-Net

Abstract: Unplanned urban settlements exist worldwide. The geospatial information of these areas is critical for urban management and reconstruction planning but usually unavailable. Automatically characterizing individual buildings in the unplanned urban village using remote sensing imagery is very challenging due to complex landscapes and high-density settlements. The newly emerging deep learning method provides the potential to characterize individual buildings in a complex urban village. This study proposed an urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…Finally, a softmax function generates the segmentation results. The model soon became widely used for medical image segmentation and also some studies can be found in urban images segmentation [100][101][102]. Yi et al [103] proposed DeepResUnet for effective urban building segmentation at pixel-scale from VHR imagery.…”
Section: Symmetrical Fcns With Skip Connectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a softmax function generates the segmentation results. The model soon became widely used for medical image segmentation and also some studies can be found in urban images segmentation [100][101][102]. Yi et al [103] proposed DeepResUnet for effective urban building segmentation at pixel-scale from VHR imagery.…”
Section: Symmetrical Fcns With Skip Connectionsmentioning
confidence: 99%
“…[106,121,140,141]. Some classified buildings to their utilities [102,113], smaller features inside roads [142] and slum area [135]. Besides the segmentation of features, the studies use different approaches to improve semantic segmentation of urban features, which are shown in Table 1.…”
Section: The Study Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…A good review of these traditional techniques can be found in [4], [5], [1]. Although these methods use the contextual spatial and spectral information of remote sensing images, the traditional manual design of image features is a tedious and complex task and it is mostly performed on the basis of domainspecific knowledge [6], [7], [8], [9]. The explosive growth of available remote sensing data and the increased processing power afforded by graphical processing units (GPUs) has led to the rise of advanced techniques based on deep learning (DL) [10], [11].…”
Section: Introductionmentioning
confidence: 99%